DARI SEORANG PEMIKIR PEMBERONTAK MENJADI MUSLIMAH PEJUANG:: Membaca Transformasi RA. Kartini - A'isyah, Siti (LPPI Universitas Al-Qolam Malang, 2019)
Kartini is one of the great figures in history who is often simply and arbitrarily simplified as a figure of female emancipation. Yet when it is understood in detail in her life history, then the spirit of heroism is seen extraordinary, not only for women, but for humans and humanity in general. This article attempts to read the phases of Kartini's thoughts and actions through reading her letters to her correspondent friends. From these letters, it was read that there was a very human process in Kartini's life journey: from a liberal and radical figure, to a down-to-earth warrior figure. This transformation process certainly occured because of the influence of the environment she had faced. External literature that supports the reading of this transformation becomes urgent to get a more comprehensive understanding.